HUBUNGAN POLA ASUH AUTORITATIF DENGAN TARAF KECEMASAN PADA SISWA AKSELERASI SMA NEGERI 1 DENPASAR - Sari, Amanda; Rustika, I Made (Jurnal Psikologi Udayana; Vol 2 No 2 (2015)DO - 10.24843/JPU.2015.v02.i02.p10, 2015)
Anxiety is a state of excessive tension is not in place, which is marked by feelings of worry, uncertain or afraid. Anxiety is able to influence health and emotional development, so it plays an important role in someone's life, even more in acceleration class which is always required high achievement. Parenting style adopted by parents determine the ability of adolescents to adapt to a variety of problems. Application of the authoritative parenting style characterized by warmth of parent-child relationship will greatly affect the ability of adolescents to overcome emotional problems.   This study aims to determine the relationship between authoritative parenting style with acceleration students’ anxiety level. Subjects in this study were all acceleration students of SMAN 1 Denpasar. The instrument used in this study is the authoritative parenting scale and the scale of anxiety. The research data were analyzed by using product moment. The correlation coefficient between authoritative parenting style with the anxiety level is -0.268 (p = 0.035), thus can be mentioned that there was a negative relationship between authoritative parenting style with anxiety level.   Keywords: authoritative parenting style, anxiety, acceleration students